Transcatheter Tricuspid Valve-In-Ring and Aortic Valve-In-Valve Implantation - Daniel Reichart; Niklas Schofer; Florian Deuschl; Andreas Schaefer; Stefan Blankenberg; Hermann Reichenspurner; Ulrich Schaefer; Lenard Conradi (The Thoracic & Cardiovascular Surgeon Reports, 2017)
Abstract